First survey of Enterocytozoon bieneusi and dominant genotype Peru6 among ethnic minority groups in southwestern China's Yunnan Province and assessment of risk factors. - Baiyan Gong; Yaming Yang; Xiaohua Liu; Jianping Cao; Meng Xu; Ning Xu; Fengkun Yang; Fangwei Wu; Benfu Li; Aiqin Liu; Yujuan Shen (Public Library of Science (PLoS), 2019)
Background Enterocytozoon bieneusi is the most common microsporidian species causing diarrhea and other intestinal disorders in humans and animals. Like other infectious diseases, microsporidiosis usually disproportionately affects poor populations. In China, some ethnic minority areas remain poor. Currently, no information of E. bieneusi infection is available in minority populations. The present aims were to understand occurrence and genetic characterizations of E. bieneusi in ethnic minority groups from a poverty-stricken ethnic township in Yunnan Province, and to assess risk factors for E. bieneusi infection. Methodology/principal findings 289 fecal specimens were collected from Yao people (one specimen each) with and without diarrhea, in Yunnan Province. E. bieneusi was identified and genotyped by PCR and sequence analysis of the ITS region of the rRNA gene. An average prevalence of 8.30% (24/289) was observed and four genotypes were identified-genotype Peru6 (n = 21) and three novel genotypes (one each). Genotype Peru6 was detected in two family members in each of three families. In a phylogenetic analysis, all of four genotypes fell into group 1 with zoonotic potential. The people owning individual pit toilets had a statistically higher prevalence of E. bieneusi (16.67%, 12/72) than those using public pit toilets (6.06%, 12/198). Conclusions/significance This is the first report on occurrence and genetic characteristics of E. bieneusi in ethnic minority groups in China. Genotype Peru6 was found in humans in China for the first time and showed dominance in Yao people. The same genotype was found in some family members and all the genotypes fell into group 1, suggesting the possibility of anthroponotic and zoonotic transmissions. The majority (83.33%, 20/24) of E. bieneusi positive individuals did not present diarrhea. In any case, it is important to recognize their existence and the importance that asymptomatic individuals to E. bieneusi may have from an epidemiological point of view, as transmitters of this pathogen. The analysis of risk factors provides scientific evidence for the development of effective strategies for prevention and control of E. bieneusi infection.